2000
DOI: 10.1161/01.hyp.36.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Angiotensin II Type 2 Receptor, Inositol 1,4,5-Trisphosphate Receptor, and Protein Kinase Cε During Cardioprotection Induced by Angiotensin II Type 2 Receptor Blockade

Abstract: Abstract-We hypothesized that the cardioprotective effect of angiotensin II type 2 receptor (AT 2 R) blockade with PD 123,319 (PD) on the recovery of left ventricular (LV) mechanical function after ischemia/reperfusion (IR) in the isolated working rat heart is associated with the enhanced expression of AT 2 R protein and mRNA as well as an increase in inositol 1,4,5-trisphosphate type 2 receptor (IP 3 R) and protein kinase C⑀ (PKC⑀) proteins. We assessed AT 2 R, angiotensin II type 1 receptor (AT 1 R), IP 3 R,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 49 publications
(41 reference statements)
3
20
1
Order By: Relevance
“…[12][13][14] Although the impact of angiotensin II type I (AT1) receptor blocker therapy on improving CHF, LV function, and clinical outcomes has been consistently demonstrated in various clinical settings, [23][24][25][26][27][28][29] the mechanism of action through which these drugs improve CHF and LV function has not been fully elucidated. 27,30,31) The primary finding in this study was that the losartan and not the simvastatin therapy significantly enhanced the PGC-1α gene expression and improved LV function. Two recent studies 32,33) reported that some AT1 receptor blockers may act as partial agonists of peroxisome proliferator activated receptor-γ.…”
Section: Discussionmentioning
confidence: 78%
“…[12][13][14] Although the impact of angiotensin II type I (AT1) receptor blocker therapy on improving CHF, LV function, and clinical outcomes has been consistently demonstrated in various clinical settings, [23][24][25][26][27][28][29] the mechanism of action through which these drugs improve CHF and LV function has not been fully elucidated. 27,30,31) The primary finding in this study was that the losartan and not the simvastatin therapy significantly enhanced the PGC-1α gene expression and improved LV function. Two recent studies 32,33) reported that some AT1 receptor blockers may act as partial agonists of peroxisome proliferator activated receptor-γ.…”
Section: Discussionmentioning
confidence: 78%
“…Various studies suggest that AT 2 is inhibitory to cell growth and perhaps even related to the induction of programmed cell death. Conversely, Xu et al 27 recently demonstrated that the cardioprotective effect of acute treatment with an AT 2 antagonist on LV functional recovery after ischemia/reperfusion in the isolated working rat heart is specifically due to AT 2 blockade. Furthermore, Mifune et al 11 reported that AT 2 stimulation increased collagen synthesis in vascular smooth muscle via a G␣ i -mediated mechanism.…”
Section: Ichihara Et Al Role Of At 2 In Lvh and Fibrosis 349mentioning
confidence: 97%
“…Although it is somewhat surprising that a significant arginase induction in coronary microvessels can be achieved within such a short period (ie, 60 minutes) of exposure to H 2 O 2 , previous studies have shown that pharmacological and pathophysiological stimulations can alter the expression of mRNA and/or protein within 60 minutes. [51][52][53][54] Interestingly, our recent studies demonstrated that vascular arginase I was upregulated leading to the impaired NO-mediated dilation in the porcine heart subjected to either chronic hypertension (8 weeks) 55 or an acute episode of ischemiareperfusion. 56 Because ROS, including H 2 O 2 , play an important role in the vascular dysfunction in hypertension 5 and ischemia-reperfusion injury, 7 it is speculated that H 2 O 2 may be the molecule that triggers the overexpression of vascular arginase and consequently leads to the impairment of NOS-mediated vascular function under these pathophysiological conditions.…”
Section: Thengchaisri Et Al Hydrogen Peroxide Impairs Coronary Arterimentioning
confidence: 99%